Antecedents of a new social venture in Portugal: the influence of education and professional background - Bernardino, Susana (2018)
The aim of this investigation is to explore the extent to which individuals’ education and professional background influences the launching of a new social ventures (SV) in Portugal. To attain this objective, empirical data were collected through an online survey to social entrepreneurs who have already launched a SV. The sample consists of individuals who were responsible for the creation of a Portuguese NGO or a SV available on the Portuguese Social Stock Exchange. For data analysis, descriptive and inferential statistics (chi-square goodnessof- fit test) were used, as well as principal components analysis. Our investigation reveals that a higher educational level stimulates the emergence of new SV. Individuals’ professional background (such as prior occupational status, professional satisfaction and entrepreneurial context) also has a positive impact on the decision-making. We also detect that individuals’ past entrepreneurial experiences shape (in an indirect way) how individuals accept the risks of launching a SV.